2005
DOI: 10.1117/12.630734
|View full text |Cite
|
Sign up to set email alerts
|

<title>Framework for effective use of multiple displays</title>

Abstract: Meeting environments, such as conference rooms, executive briefing centers, and exhibition spaces, are now commonly equipped with multiple displays, and will become increasingly display-rich in the future. Existing authoring / presentation tools such as PowerPoint, however, provide little support for effective utilization of multiple displays. Even using advanced multi-display enabled multimedia presentation tools, the task of assigning material to displays is tedious and distracts presenters from focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The findings of those studies indicated some evidence of drawbacks in slideware applications such as PowerPoint and Impress. The static, linear, single frame-by-frame, and presenter-centered presentation are the characteristics of the popular slideware applications that are viewed by some researchers as the dominant drawbacks of such applications [26][27][28][29][30][31]. Subsequently, many researches and studies have been conducted to overcome those drawbacks by improving and enhancing the slideware application, which finally lead to the development of presentation system.…”
Section: B Live Multimedia Presentationmentioning
confidence: 99%
“…The findings of those studies indicated some evidence of drawbacks in slideware applications such as PowerPoint and Impress. The static, linear, single frame-by-frame, and presenter-centered presentation are the characteristics of the popular slideware applications that are viewed by some researchers as the dominant drawbacks of such applications [26][27][28][29][30][31]. Subsequently, many researches and studies have been conducted to overcome those drawbacks by improving and enhancing the slideware application, which finally lead to the development of presentation system.…”
Section: B Live Multimedia Presentationmentioning
confidence: 99%
“…There also exist first presentation systems that support the simultaneous display of multiple slides on large interactive screens and in multi-display environments [14][15][16]. Depending on the used approach, contents are either organized with respect to a prepared temporal ordering, similar to classic slideware (see, e.g., [14,17]), or with respect to the subject matter, resulting in a content-oriented modeling (see, e.g., [18,19]).…”
Section: Introductionmentioning
confidence: 99%
“…The slides can also be manipulated and annotated in a simple and flexible way. Liu et al [21] created an EPIC. It views and treats all type of multimedia elements as a (hyper) slide.…”
Section: Related Workmentioning
confidence: 99%
“…Liu et.al. [21] developed a presentation system called EPIC. They view and treat all types of multimedia data as a (hyper) slide.…”
Section: The Proposed Model Of Lmpmentioning
confidence: 99%
See 1 more Smart Citation